Exercise and Vitamin D Supplementation Modify Spleen Morphology in Lean, but not, in Monosodium-Glutamate-Obese Rats - Maria Guareschi, Zoé; Marieli Ceglarek, Vanessa; Fontes Rodrigues, Patrick; Pierre Huning, Luiz; Festinalli, Cintia; Paulo de Arruda Amorim, João; Grassiolli, Sabrina (Journal of Spleen And Liver Research, 2019)
An experimental study examines how exercise and vitamin D supplementation affect spleen morphology in lean versus MSG‑obese rats, discussing immunologic implications.
Keywords: Swimming; spleen; vitamin D; obesity; histomorphometry